Identification of vibrational excitations and optical transitions of the organic electron donor tetraphenyldibenzoperiflanthene (DBP). Issue 45 (28th October 2015) - Rouillé, Gaël; Kirchhuebel, Tino; Rink, Marcel; Gruenewald, Marco; Kröger, Jörg; Forker, Roman; Fritz, Torsten
Abstract : The spectra of DBP grains (IR) and rare-gas-matrix-isolated molecules (UV/vis) are used to analyze HREELS and DRS measurements of DBP molecules adsorbed on Au(111) and mica(0001). Abstract : Tetraphenyldibenzoperiflanthene (DBP) attracts interest as an organic electron donor for photovoltaic applications. In order to assist in the analysis of vibrational and optical spectra measured during the formation of thin films of DBP, we have studied the vibrational modes and the electronic states of this molecule. Information on the vibrational modes of the electronic ground state has been obtained by IR absorption spectroscopy of DBP grains embedded in polyethylene and CsI pellets and by calculations using density functional theory (DFT). Electronic transitions have been measured by UV/vis absorption spectroscopy applied to DBP molecules isolated in rare-gas matrices. These measurements are compared with the results of ab initio and semi-empirical calculations. Particularly, the vibrational pattern observed in the S1 ← S0 transition is interpreted using a theoretical vibronic spectrum computed with an ab initio model. The results of the previous experiments and calculations are employed to analyze the data obtained by high-resolution electron energy loss spectroscopy (HREELS) applied to DBP molecules deposited on a Au(111) surface. They are also used to examine the measurements performed by differential reflectance spectroscopy (DRS) on DBP molecules deposited on a muscovite mica(0001) surface. It is concluded that the DBP molecules in the first monolayer do not show any obvious degree of chemisorption on mica(0001). Regarding the first monolayer of DBP on Au(111), the HREELS data are consistent with a face-on anchoring and the absence of strong electronic coupling.